CURRENT ISSUES OF INCREASING THE EFFICIENCY OF PHYSICAL EDUCATION (Physical Culture and Sport: Scientific Perspective, 2024)
The article examines the data devoted to the design of the content of continuous physical exercises, which depend on general well-being, physical fitness, work capacity, mental activity, psychological and emotional state, and the desire for better results in various spheres of activity.The problem of improving the training of specialists in the field of physical education and sports is becoming more and more urgent every year. The main purpose of physical education is to strengthen health, ensure and improve general physical fitness, eliminate functional deviations, nurture and improve physical qualities, and form professional and applied skills and abilities necessary for future professional activities.The system of physical education is not only related to the acquisition of knowledge, but is a set of elements of physical culture ordered in relation to the purpose of the activity. In our difficult wartime, the search for ways to improve the educational process to the maximum approximation of the effectiveness of physical education in order to create a health-preserving environment and restore the physical and psychological state is intensively underway.Educational activity consists in ensuring two main processes - accumulating one's own experience and transferring it in an accessible form to the younger generation. Special attention should be paid to the personal approach, which provides understanding, knowledge, development and self-realization to improve the integrity and harmony of the individual.The content of professional training defines the training technologies, which are considered as part of the training process, which ensures the functioning of the system in accordance with the set goals of the students who are engaged in physical culture.In order to increase the effectiveness of physical exercises, it is necessary to skillfully combine training and pedagogical activities, thereby increasing motivation for physical culture and one's own successes and achievements.
Keywords: physical education; physical exercises; physical culture; physical development; teacher; classes; health; physical qualities